A presença inglesa no Brasil e sua influência nas obras de escritores brasileiros do século XIX - PEREIRA, Rosamaria Reo (2005)
This thesis has the main objective to investigate the presence of the English writers on the works of the Brazilian writers of the XIX century. The English novelists who were important at that time were Daniel Defoe, Samuel Richardson and Henry Fielding. They contributed to the rising and consolidation of the novel as a literary genre. In Brasil, the novel developed itself with a greater freedom and attracted the public reader. The new public started to read the novels which re-created the cities, the streets and the lives of the people who were emerging from a social class called: bourgeoisie. The new genre which appears in England increased business, with the proliferation of magazines and newspapers of popular and literary topics. The Brazilian writers such as José de Alencar and Machado de Assis were influenced by these English writers; however, this influence was not only reflected on the novels of those writers, but also on business, on culture and on the social life in Brazil. Some narratives, written by José de Alencar, show in a subtle way, the British influence, their habits and customs over the economic, political and cultural life of Brazil of the XIX century. Some other examples of this presence are reveled on the works of Machado de Assis through quotations, references and allusions. Machado de Assis in his novels does some references to English writers either from the XVI and XVIII century or from the XIX century, such as Shakespeare, Swift, Fielding, Sterne, Lamb and Dickens, among other English writers.